Usage, Pleasure, Price, and Feeling: A Study on Shopping Orientation and Consumer Outcome - Zhao, Shaoqiong; Chen, Pu; Zhu, Yan; Wei, Feng; Liu, Fangmei (Frontiers in Psychology, 2022)
Understanding consumers’ behavior has been a research focus for the past decades, especially for the purchase-related behavior which they are facing in their daily lives. Products as the most important element in the purchase process impact consumers’ purchase patterns. Such as products classifications, usages, prices, and feelings, etc. are highly related to consumers’ behavior. Both researchers and practitioners are curious to know how purchase patterns are different in these conditions. The primary focus of this research examined how the price of the products influences consumers’ purchase behavior across hedonic and utilitarian categories under regulatory focus theory (RFT). The secondary insight was to examine how mood can moderate this impact. We conducted three experimental studies to examine these research questions regarding consumers’ preference of hedonic (utilitarian) products when the price is low (high) and at different mood conditions in this purchase process. In the last section, we discussed the theoretical contribution, strategic insights for product designers and marketers, and possible future research directions.